1989
DOI: 10.1055/s-2008-1046990
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Volumenbestimmungen auf MR-Tomogrammen beim kommunizierenden Hydrozephalus

Abstract: For patients with communicating hydrocephalus the implantation of a cardioventricular shunt is mostly an approved therapy. However, indications are frequently problematic and therefore a shunt operation will not be always successful. The proof of periventricular oedemas in addition to clinical signs seems to be a criterion for an indication for implantation and for the selection of a special valve. With the aid of a newly developed computer programme volume estimation of the ventricular system and the perivent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the normal human brain, small fractions of CSF diffuse into the brain tissue as CSF and ISF communicate freely (21). Periventricular edema in hydrocephalic brain can be detected by looking for PVH (7) and is the result of an increased compensatory CSF flow into the periventricular WM (22). In NPH, PVH are found in many but not all patients, e.g., Krauss et al (23) reported no PVH in 17.1% of 41 patients with confirmed NPH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the normal human brain, small fractions of CSF diffuse into the brain tissue as CSF and ISF communicate freely (21). Periventricular edema in hydrocephalic brain can be detected by looking for PVH (7) and is the result of an increased compensatory CSF flow into the periventricular WM (22). In NPH, PVH are found in many but not all patients, e.g., Krauss et al (23) reported no PVH in 17.1% of 41 patients with confirmed NPH.…”
Section: Discussionmentioning
confidence: 99%
“…Tullberg et al (5) reported that especially an irregular type of PVH around the frontal horns diminishes after shunt surgery in contrast to smooth PVH. In most cases hyperintensities are only analyzed for the presence, size, and confluence (6) or by the total volume fraction of periventricular hyperintensities compared to the volume fraction of the brain parenchyma (7).…”
mentioning
confidence: 99%